2015
DOI: 10.5194/acpd-15-2679-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secondary Organic Aerosol (SOA) formation from the β-pinene + NO<sub>3</sub> system: effect of humidity and peroxy radical fate

Abstract: Abstract. The formation of secondary organic aerosol (SOA) from the oxidation of β-pinene via nitrate radicals is investigated in the Georgia Tech Environmental Chamber facility (GTEC). Aerosol yields are determined for experiments performed under both dry (RH < 2%) and humid (RH = 50% and RH = 70%) conditions. To probe the effects of peroxy radical (RO2) fate on aerosol formation, "RO2 + NO3 dominant" and "RO2 + HO2 dominant" experiments are performed. Gas-phase organic nitrate species (with molecular weig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 136 publications
5
84
2
Order By: Relevance
“…For these three oxidation channels, RH has little effect on SOA yields from OH channel oxidization. Previous studies have shown that humidity has little effect on SOA formation from NO 3 oxidation of alkenes (Bonn and Moorgat, 2002;Fry et al, 2009;Boyd et al, 2015). Thus, only the O 3 channel is greatly influenced by RH.…”
Section: Soa Yieldsmentioning
confidence: 93%
“…For these three oxidation channels, RH has little effect on SOA yields from OH channel oxidization. Previous studies have shown that humidity has little effect on SOA formation from NO 3 oxidation of alkenes (Bonn and Moorgat, 2002;Fry et al, 2009;Boyd et al, 2015). Thus, only the O 3 channel is greatly influenced by RH.…”
Section: Soa Yieldsmentioning
confidence: 93%
“…Gas-phase production with dynamic gas-particle partitioning followed by rapid loss, such as by photolysis (28,29), heterogeneous hydrolysis (30)(31)(32)(33), or reaction with the hydroxyl radical (OH) (34,35), could potentially operate on such timescales and have different patterns as a function of time of day between the C 5 and C 10 groups. We note that the volatile organic compound + NO 3 and RO 2 + NO reactions produce varying levels of primary/secondary vs. tertiary ONs, all of which having different hydrolysis rates (30,32,33). Thus, the overall contribution of the various loss pathways to pON lifetime warrants additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of particulate organic nitrates (pON) to measured nitrate has been estimated using the method described in Fry et al (2009) for the SEAC 4 RS flights on which the HR-ToF-AMS was operated . The pON, likely in the form of oxidized monoterpene nitrates (Boyd et al, 2015;Draper et al, 2015;Xu et al, 2015a, b), is estimated to be between 15 and 40 % of the total measured nitrate above the surface in the well-mixed and transition layers, and more than 63 % across the southeastern US at the surface (Xu et al, 2015a). However, nitrate represented < 5 % of fine aerosol mass in the data analyzed here.…”
Section: A Brock Et Al: Aerosol Optical Properties In the Southementioning
confidence: 99%